Effects of recreational scuba diving on Mediterranean fishes: evidence of involuntary feeding? - DI FRANCO, A.; BAIATA, P.; MILAZZO, M. (Mediterranean Marine Science, 2013)
Despite a large body of literature assessing the impacts of recreational scuba diving on marine habitats, little attention has been paid to the potentially harmful effects this has on fishes. The aim of this study was the assessment of the immediate response of different fish species to divers’ activities. A decrease of fishes’ natural diffidence towards divers is shown, probably due to an enhanced availability of their prey as a result of divers’ contacts with the substrate.